BS ISO 7432. Glass-reinforced thermosetting plastics (GRP) pipes and fittings. Test methods to prove the design of locked socket-and-spigot joints, including double-socket joints, with elastomeric seals. (4th August 2020) - British Standards Institution,
No abstract available